Smart Card Research and Advanced Applications VI IFIP 18th World Computer Congress TC8/WG8.8 & TC11/WG11.2 Sixth International Conference on Smart Card Research and Advanced Applications (CARDIS) 22–27 August 2004 Toulouse, France - Quisquater, Jean-Jacques; Paradinas, Pierre; Deswarte, Yves; Abou El Kalam, Anas (Springer US, 2004)
Smart Card Research and Advanced Applications VI Edited by Jean-Jacques Quisquater, Pierre Paradinas, Yves Deswarte, and Anas Abou El Kalam In the Information Society, the smart card, or smart device with its processing power and link to its owner, will be the potential human representation or delegate in Ambient Intelligence (Pervasive Computing), where every appliance or computer will be connected, and where control and trust of the personal environment will be the next decade challenge. Smart card research is of increasing importance as the need for information security grows rapidly. Smart cards will play a very large role in ID management in secure systems. In many computer science areas, smart cards introduce new dimensions and opportunities. Disciplines like hardware design, operating systems, modeling systems, cryptography and distributed systems find new areas of applications or issues; smart cards also create new challenges for these domains.
Keywords: Artificial Intelligence; Artificial intelligence; Chipkarte; Konferenzschrift -- 2004 -- Toulouse